Method for preparing tungsten-copper heat sink material from tungsten-copper composite powder and tungsten-copper heat sink material

The preparation of copper-tungsten composite powder by sol-gel method and combined with injection molding and degreasing sintering processes, the problems of high production cost and low density of existing tungsten copper heat sink materials are solved, and efficient and economical preparation of tungsten copper heat sink materials are achieved, thereby improving the density and thermal conductivity of the material.

CN119876667APending Publication Date: 2025-04-25XIAN SIRUI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411912855.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing tungsten copper heat sink preparation process has high production costs, complex shapes and requires a lot of machining, and the tungsten skeleton has problems such as increasing machining difficulty. In addition, the removal effect of paraffin and wax-based adhesives in injection molding slurry or feeding is poor and the density is low.

Method used

The copper-tungsten composite powder was prepared by the sol-gel method, and the pelletization was performed by adding plastic-based binder to a nitrogen atmosphere for pelletization to obtain a copper-tungsten feed with a particle size of 1 to 3 μm. Then, the tungsten copper heat sink material was prepared by injection molding and degreasing sintering, and a spider-web-type groove was set in the injection molding semi-finished product to increase the heat conduction path.

Benefits of technology

It reduces production costs, simplifies the machining process, improves the density and thermal conductivity of the material, ensures the performance stability of the product, and effectively disperses heat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876667A_ABST
    Figure CN119876667A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat sink materials, in particular to a method for preparing a tungsten-copper heat sink material from tungsten-copper composite powder, which comprises the following steps: S1, banburying and granulating; s2, injection molding; s3, degreasing and sintering; the invention also discloses the copper-tungsten heat sink material prepared by the method. According to the invention, 5520 or 4520 polyformaldehyde with general flowability is adopted, and the polyformaldehyde with high flowability fluctuates greatly along with the temperature change, so that the injection amount is difficult to control when a thin-wall heat sink product is subjected to injection molding; the POM main body with low fluidity is matched with the ethylene bis stearamide, the phosphotungstic heteropoly acid and the salicylic acid, so that the overall stability of the adhesive is ensured, the flow velocity of the melt is increased to be more than 1300g / 10min, and the tungsten-copper heat sink material with better dimensional precision and better compactness can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat sink materials, and in particular to a method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder and the tungsten-copper heat sink material. Background Art

[0002] In the prior art, tungsten-copper heat sink materials are prepared by melt infiltration. However, melt infiltration requires sintering of tungsten skeletons for debonding, and melting copper to fill the gaps in the tungsten skeletons to obtain tungsten-copper alloys. However, heat sink materials often have complex shapes and require a lot of machining to obtain products that meet customer needs. The presence of the tungsten skeleton increases the difficulty of machining and high production costs.

[0003] The injection molding process is a powder metallurgy near-net molding technology. The powder and the binder are mixed and kneaded to obtain the feed. After injection molding, degreasing and sintering, a blank close to customer needs is obtained. The burrs are then removed through a small amount of machining, which solves the problem of high production cost of the melt infiltration process.

[0004] CN115464144B introduces a process for injection molding of tungsten-copper-tungsten mixed powder, wherein a solid-liquid mixture of tungsten powder and copper solution is reduced in a hydrogen flow to obtain a tungsten-copper mixed powder, and then a feed is prepared and injection molded. However, this injection molding slurry or feed contains paraffin, the wax-based binder removal effect is poor, and the product density is low. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder and a tungsten-copper heat sink material.

[0006] In a first aspect, the present application protects a method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder, comprising the following steps:

[0007] S1. Mixing and granulation:

[0008] Add a plastic-based binder to a copper-tungsten composite powder in which W accounts for 60-95wt% in a nitrogen atmosphere with an oxygen content of less than 0.01%, stir and knead for 1.5-3h at 170-180°C and 30-50r / min to obtain a mixture, extrude and chop it, and obtain a copper-tungsten feed with a particle size of 1-3μm;

[0009] The amount of the plastic-based binder added is 10-15wt% of the mixture, and the plastic-based binder, by mass percentage, includes: 3-5% high-density polyethylene, 3-6% ethylene bisstearamide, 0.5-2% phosphotungstic heteropoly acid, 0.5-2% salicylic acid, and the balance polyformaldehyde, wherein the polyformaldehyde is any one or more of polyformaldehyde 5520 and polyformaldehyde 4520;

[0010] S2. Injection molding:

[0011] The mold is preheated to 75-95° C., the copper-tungsten feed obtained in step S1 is softened at a temperature of 145-170° C. for 2-3.5 hours, and then the softened copper-tungsten feed is injected into the mold at a pressure of 80-120 MPa, and the pressure is maintained for 1-3 seconds, and then demolded to obtain an injection molded semi-finished product;

[0012] S3, degreasing and sintering:

[0013] After degreasing the injection molded semi-finished product obtained in step S2, the temperature is continuously raised to 1080-1200° C. at a rate of 1-3° C. / min and kept at this temperature for 4-6 hours to obtain a tungsten-copper heat sink material.

[0014] Furthermore, the preparation method of the copper-tungsten composite powder comprises the following steps:

[0015] ammonium paratungstate, soluble copper salt and organic acid solution are mixed in a mass ratio of 12:25-300:60-756 to obtain a gel, and the gel is dried at 250-400° C. to obtain a precursor powder;

[0016] The precursor powder is calcined at 500-700° C. for 3-6 hours to obtain a copper-tungsten composite oxide, and then the copper-tungsten composite oxide is reduced at 750-880° C. for 3-5 hours in a hydrogen-containing atmosphere to obtain a copper-tungsten composite powder;

[0017] Description: Copper-tungsten composite powder is prepared by sol-gel method. The surface of tungsten particles is coated with a uniform copper layer, which avoids the problem of tungsten particles contacting and agglomerating due to the tungsten particles not being coated by the copper layer, and ensures the stability of the comprehensive performance of the heat sink material product.

[0018] Furthermore, the soluble copper salt is selected from any one of copper nitrate and copper sulfate, and the organic acid solution is a citric acid solution with a mass concentration of 50-60%.

[0019] Description: Taking advantage of the fact that solutions can easily mix different soluble substances evenly, tungsten and copper are prepared into composite powder in the solution, thus avoiding the problem of uneven mechanical powder mixing and unstable performance of heat sink material products.

[0020] Furthermore, the hydrogen-containing atmosphere is any one of hydrogen, hydrogen-argon mixed gas or hydrogen-carbon monoxide mixed gas, wherein the hydrogen content is 95-100%.

[0021] Note: Hydrogen can be used as a reducing agent to reduce tungsten oxide to metallic tungsten, which is very important for the preparation of high-purity copper-tungsten materials.

[0022] Furthermore, the method for mixing to obtain the gel is: stirring at 70 to 95° C. at a frequency of 30 to 60 Hz for 1 to 2 hours to obtain the gel.

[0023] Note: Too low temperature and mixing parameters may lead to incomplete reaction, making the composition of copper-tungsten gel uneven, affecting its physical and chemical properties; too high temperature and mixing parameters may lead to overreaction, causing the composition of copper-tungsten gel to change, affecting its stability and reliability.

[0024] Furthermore, the particle size of the precursor powder is 0.2-1.5 μm, and the particle size of the copper-tungsten composite powder is 200-700 nm.

[0025] Note: Uneven distribution of the particle size of the precursor powder, or a large difference from the particle size after reduction, may lead to uneven distribution of copper and tungsten in the final material, thus affecting the performance of the material.

[0026] Furthermore, after obtaining the gel, the gel is divided into a first gel and a second gel with a mass ratio of 1:2 to 4, and the first gel is axially stretched with a stretching multiple of 3 to 8 times to obtain the stretched first gel; the second gel is then directionally frozen at -40 to -100°C for 18 to 20 hours, and then restored to room temperature and axially stretched with a stretching multiple of 5 to 7 times to obtain the freeze-stretched second gel, and the stretched first gel is used as the core and the freeze-stretched second gel is used as the core-shell, and the two are mixed to obtain a core-shell type gel.

[0027] Description: The core part is stretched to make the internal copper tungsten particles more orderly, forming a channel that is conducive to heat conduction. The core-shell part is frozen and then stretched to form a special particle arrangement at the microscopic level. This structure can further promote the conduction of heat in the core-shell part, and work together with the core part, which is conducive to the rapid transfer of heat from the core to the core-shell part, and the thermal conductivity is enhanced; and the core-shell structure can better resist external pressure, vibration and other mechanical interference.

[0028] Further, in step S2, the method of injecting the softened copper-tungsten feed into the mold is:

[0029] The copper tungsten feed is divided into 1-2μmA copper tungsten feed and 2-3μmB copper tungsten feed according to particle size;

[0030] 1 / 2 to 3 / 4 of A copper-tungsten feed and 1 / 2 to 3 / 4 of B copper-tungsten feed are mixed and injected into the mold at 50 to 80 MPa, and the pressure is maintained for 1 to 3 seconds to serve as the bottom layer, and then a spider-web-shaped groove is etched on the surface of the bottom layer, and the depth of the spider-web-shaped groove is 1 / 2 to 3 / 5 of the thickness of the bottom layer; wherein the center of the spider-web-shaped groove coincides with the center of the bottom layer, and the minimum radius of the spider-web-shaped groove is 1 / 8 to 1 / 10 of the length of the bottom layer, and the radius of each circle of the spider-web-shaped groove is 1.2 to 1.3 times the radius of the previous circle from the inside to the outside, and the skeleton line of the spider-web-shaped groove is radially arranged along the minimum radius, and 10 to 15 skeleton lines are arranged at equal angles;

[0031] Finally, the remaining A copper tungsten feed and B copper tungsten feed are injected into the groove with the same injection parameters as the bottom layer, and the injection is completed.

[0032] Description: The layered setting of the bottom and upper copper tungsten feed materials, plus the existence of spider-web-shaped grooves, increases the path of heat conduction. When heat is conducted from the bottom to the upper filling part, it can be conducted through more contact surfaces and paths. The groove structure can reduce the thermal resistance in the heat conduction process, so that heat can be transferred from the heat source to various parts of the heat sink material with higher efficiency. Compared with a single-structure heat sink material, it can disperse the heat more effectively.

[0033] Furthermore, in step S3, the degreasing method is: under a nitrogen atmosphere, adding oxalic acid with a mass concentration of 10-20% at a rate of 2-5 g / min to the injection molded semi-finished product obtained in step S2, degreasing at 110-130° C. for 2-4 hours, and then continuously heating to 580-620° C. at 1-3° C. / min in a hydrogen atmosphere and keeping the temperature for degreasing for 2-3 hours.

[0034] Description: Combine oxalic acid degreasing and thermal degreasing to reduce binder residues.

[0035] In a second aspect, the present application also protects a tungsten-copper heat sink material, which is prepared by any one of the preparation processes in the first aspect.

[0036] Compared with the existing tungsten copper heat sink material, the beneficial effects of the present invention are:

[0037] (1) Compared with the low crystallinity and high fluidity copolymer formaldehyde often used in the existing process, the plastic-based binder used in this application uses 5520 or 4520 polyformaldehyde with average fluidity. This is because the high fluidity polyformaldehyde fluctuates greatly with temperature changes, which makes it difficult to control the injection volume when injection molding thin-walled heat sink products. By combining the low fluidity POM main body with ethylene bisstearamide, phosphotungstic heteropoly acid, and salicylic acid, the melt flow rate is increased to more than 1300g / 10min while ensuring the overall stability of the binder.

[0038] (2) The present application aims to solve the problem of unstable comprehensive performance caused by uneven mixing of existing tungsten-copper heat sink materials. A copper-tungsten composite powder is prepared by a sol-gel method. When preparing a core-shell gel, the core part is stretched to make the internal copper-tungsten particles more orderly, forming a channel that is conducive to heat conduction. The core-shell part is frozen and then stretched to form a special particle arrangement at the microscopic level. This structure can further promote the conduction of heat in the core-shell part, and work together with the core part, which is conducive to the rapid transfer of heat from the core to the core-shell part, thereby enhancing thermal conductivity. In addition, the core-shell structure can better resist external pressure, vibration and other mechanical interference.

[0039] (3) When preparing the injection molded semi-finished product, the present application first uses part of the copper-tungsten feed as the bottom layer, and the remaining copper-tungsten feed fills the spider-web-shaped grooves on the bottom layer and is compounded with the bottom layer, thereby increasing the heat conduction path. When heat is conducted from the bottom layer to the upper filling part, it can be conducted through more contact surfaces and paths. The groove structure can reduce the thermal resistance in the heat conduction process, so that heat can be transferred from the heat source to various parts of the heat sink material with higher efficiency. Compared with a heat sink material with a single structure, it can disperse the heat more effectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a 500-fold electron microscope micrograph of the copper-tungsten heat sink material of the present invention;

[0041] Figure 2 This is a 1000-fold electron microscope micrograph of the copper-tungsten heat sink material of the present invention;

[0042] Figure 3 A metallographic micrograph that is 100 times larger than the copper-tungsten heat sink material of the present invention;

[0043] Figure 4 A metallographic micrograph that is 200 times larger than the copper-tungsten heat sink material of the present invention;

[0044] Figure 5 The metallographic micrograph is 100 times larger than the copper-tungsten heat sink material prepared by the conventional infiltration process;

[0045] Figure 6 The metallographic micrograph is 200 times larger than the copper-tungsten heat sink material prepared by the conventional infiltration process. DETAILED DESCRIPTION

[0046] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0047] Embodiment 1: A method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder, comprising the following steps:

[0048] The preparation method of copper-tungsten composite powder is as follows:

[0049] Ammonium paratungstate with a tungsten trioxide content of 88%, copper nitrate, and a citric acid solution with a mass concentration of 55 g / L were stirred at a mass ratio of 19:50:130 at a frequency of 45 Hz for 1.5 hours at 80°C to obtain a gel, and the gel was dried at 320°C to obtain a precursor powder with a particle size of 0.6 to 1.0 μm;

[0050] The precursor powder is calcined at 600° C. for 4.5 hours to obtain a copper-tungsten composite oxide, and then the copper-tungsten composite oxide is reduced at 810° C. for 4 hours in a hydrogen atmosphere to obtain a copper-tungsten composite powder with a particle size of 360 to 520 nm;

[0051] S1. Mixing and granulation:

[0052] In a nitrogen atmosphere with an oxygen content of less than 0.01%, a plastic-based binder is added to a copper-tungsten composite powder in which W accounts for 80wt%, and the mixture is stirred and kneaded at 175°C and 40r / min for 2h to obtain a mixture, which is extruded and chopped to obtain a copper-tungsten feed with a particle size of 1 to 3μm;

[0053] The amount of the plastic-based binder added is 12.5wt% of the mixture, and the plastic-based binder, by mass percentage, includes: 4% high-density polyethylene, 4.5% ethylene bisstearamide, 1% phosphotungstic heteropoly acid, 1% salicylic acid, and the balance polyformaldehyde, wherein the polyformaldehyde is polyformaldehyde 5520;

[0054] S2. Injection molding:

[0055] The mold is preheated to 80° C., the copper-tungsten feed obtained in step S1 is softened at 155° C. for 3 h, and then the softened copper-tungsten feed is injected into the mold at 100 MPa and maintained at a pressure of 2 s, and then demolded to obtain an injection molded semi-finished product;

[0056] S3, degreasing and sintering:

[0057] After degreasing the injection molding semi-finished product obtained in step S2, the degreasing method is as follows: in a nitrogen atmosphere, oxalic acid with a mass concentration of 15% is added to the injection molding semi-finished product obtained in step S2 at a rate of 3.5 g / min, degreasing at 120° C. for 3 hours, and then continuously heating to 600° C. at 2° C. / min in a hydrogen atmosphere and degreasing for 2.5 hours.

[0058] The temperature was then raised to 1120°C at a rate of 2°C / min and kept at that temperature for 5 hours to obtain a tungsten-copper heat sink material.

[0059] Example 2: A tungsten-copper heat sink material is prepared according to the method for preparing a tungsten-copper heat sink material using tungsten-copper composite powder in Example 1, wherein W accounts for 80wt%, the density is 96.12%, and the thermal conductivity is 260.01W / (M*K).

[0060] Example 3: The difference between this example and Example 1 is that a plastic-based binder is added to a copper-tungsten composite powder in which W accounts for 60wt% (wherein the mass ratio of ammonium paratungstate with a tungsten trioxide content of 88%, copper nitrate, and a citric acid solution with a mass concentration of 50g / L is 12:25:75), and the mixture is stirred and kneaded at 170°C and 30r / min for 1.5h to obtain a copper-tungsten feed with a particle size of 1-3μm.

[0061] Example 4: The difference between this example and Example 1 is that a plastic-based binder is added to a copper-tungsten composite powder in which W accounts for 95wt% (wherein the mass ratio of ammonium paratungstate with a tungsten trioxide content of 88%, copper nitrate, and a citric acid solution with a mass concentration of 60g / L is 1:25:51), and the mixture is stirred and kneaded at 180°C and 50r / min for 3h to obtain a copper-tungsten feed with a particle size of 1-3μm.

[0062] Example 5: This example is different from Example 1 in that the amount of the plastic-based binder added is 10wt% of the mixture. The plastic-based binder, calculated by mass percentage, includes: 3% high-density polyethylene, 3% ethylene bisstearamide, 0.5% phosphotungstic heteropoly acid, 0.5% salicylic acid and the remainder polyformaldehyde.

[0063] Example 6: This example is different from Example 1 in that the amount of the plastic-based binder added is 15wt% of the mixture. The plastic-based binder, calculated by mass percentage, includes: 5% high-density polyethylene, 6% ethylene bisstearamide, 2% phosphotungstic heteropoly acid, 2% salicylic acid and the remainder polyformaldehyde.

[0064] Example 7: This example is different from Example 1 in that ammonium paratungstate, soluble copper salt, and organic acid solution are stirred at 70° C. and 30 Hz for 1 h to obtain a gel, and the gel is dried at 250° C. to obtain a precursor powder.

[0065] Example 8: This example is different from Example 1 in that ammonium paratungstate, soluble copper salt, and organic acid solution are stirred at 95° C. at a frequency of 60 Hz for 2 h to obtain a gel, and the gel is dried at 400° C. to obtain a precursor powder.

[0066] Example 9: This example is different from Example 1 in that the precursor powder is calcined at 500°C for 3 hours to obtain copper-tungsten composite oxide, and then the copper-tungsten composite oxide is reduced at 750°C for 3 hours in a hydrogen-containing atmosphere to obtain copper-tungsten composite powder.

[0067] Example 10: This example is different from Example 1 in that the precursor powder is calcined at 700°C for 6 hours to obtain copper-tungsten composite oxide, and then the copper-tungsten composite oxide is reduced at 880°C for 5 hours in a hydrogen-containing atmosphere to obtain copper-tungsten composite powder.

[0068] Example 11: This example is different from Example 1 in that the particle size of the precursor powder is 0.2-0.6 μm, and the particle size of the copper-tungsten composite powder is 520-700 nm.

[0069] Example 12: This example is different from Example 1 in that the particle size of the precursor powder is 1.0-1.5 μm, and the particle size of the copper-tungsten composite powder is 200-360 nm.

[0070] Example 13: This example is different from Example 1 in that the mold is preheated to 75°C, and the copper tungsten feed obtained in step S3 is softened at 145°C for 2h.

[0071] Example 14: This example is different from Example 1 in that the mold is preheated to 95°C, and the copper tungsten feed obtained in step S3 is softened at 170°C for 3.5 hours.

[0072] Example 15: This example is different from Example 1 in that the pressure is maintained at 80 MPa for 1 second.

[0073] Example 16: This example is different from Example 1 in that the pressure is maintained at 120 MPa for 3 seconds.

[0074] Example 17: This example differs from Example 1 in that, under a nitrogen atmosphere, oxalic acid with a mass concentration of 10% is added to the injection molded semi-finished product obtained in step S2 at a rate of 2 g / min, and degreasing is carried out at 110°C for 2 hours.

[0075] Example 18: This example differs from Example 1 in that, under a nitrogen atmosphere, oxalic acid with a mass concentration of 20% is added to the injection molded semi-finished product obtained in step S2 at a rate of 5 g / min, and degreasing is carried out at 130°C for 4 hours.

[0076] Example 19: This example is different from Example 1 in that the temperature is continuously raised to 580°C at 1°C / min in a hydrogen atmosphere and kept for degreasing for 2 hours.

[0077] Example 20: This example is different from Example 1 in that the temperature is continuously raised to 620°C at 3°C / min in a hydrogen atmosphere and kept for degreasing for 3 hours.

[0078] Example 21: This example is different from Example 1 in that the temperature is continued to be raised to 1080°C at 1°C / min and kept at this temperature for 4 hours.

[0079] Example 22: This example differs from Example 1 in that the temperature is further increased to 1200°C at a rate of 3°C / min and maintained for 6 hours.

[0080] Example 23: The difference between this example and Example 1 is that after obtaining the gel, the gel is divided into a first gel and a second gel with a mass ratio of 1:3, and the first gel is axially stretched with a stretching multiple of 6 times to obtain the stretched first gel; the second gel is then directionally frozen at -70°C for 19 hours, and then restored to room temperature and axially stretched with a stretching multiple of 6 times to obtain the freeze-stretched second gel; the stretched first gel is used as the core, and the freeze-stretched second gel is used as the core-shell, and mixed to obtain a core-shell type gel.

[0081] Example 24: This example is different from Example 23 in that the gel is divided into a first gel and a second gel with a mass ratio of 1:2.

[0082] Example 25: This example is different from Example 23 in that the gel is divided into a first gel and a second gel with a mass ratio of 1:4.

[0083] Example 26: This example is different from Example 23 in that the first gel is axially stretched by 3 times.

[0084] Example 27: This example differs from Example 23 in that the first gel is axially stretched by 8 times.

[0085] Example 28: This example differs from Example 23 in that the second gel is directionally frozen at -40°C for 18 hours, and then axially stretched after returning to room temperature, with a stretching ratio of 5 times.

[0086] Example 29: This example differs from Example 23 in that the second gel is directionally frozen at -100°C for 20 hours, and then axially stretched after returning to room temperature, with a stretching ratio of 7 times.

[0087] Embodiment 30: This embodiment differs from Embodiment 23 in that, in step S2, the method for injecting the softened copper-tungsten feed into the mold is:

[0088] The copper tungsten feed is divided into 1-2μmA copper tungsten feed and 2-3μmB copper tungsten feed according to particle size;

[0089] 5 / 8 of A copper-tungsten feed and 5 / 8 of B copper-tungsten feed were mixed and injected into the mold at 65MPa and maintained for 2s as the bottom layer, and then a spider-web-shaped groove was etched on the surface of the bottom layer. The depth of the spider-web-shaped groove was 11 / 20 of the thickness of the bottom layer; wherein the center of the spider-web-shaped groove coincided with the center of the bottom layer, and the minimum radius of the spider-web-shaped groove was 1 / 40 of the length of the bottom layer. The radius of each circle of the spider-web-shaped groove was 1.25 times the radius of the previous circle from the inside to the outside, and the skeleton line of the spider-web-shaped groove was radially arranged along the minimum radius, and 12 skeleton lines were arranged at equal angles.

[0090] Finally, the remaining A copper tungsten feed and B copper tungsten feed are injected into the groove with the same injection parameters as the bottom layer, and the injection is completed.

[0091] Example 31: This example differs from Example 30 in that 1 / 2 of copper tungsten feed material A and 3 / 4 of copper tungsten feed material B are mixed and injected into the mold at 50 MPa, and the pressure is maintained for 1 second.

[0092] Example 32: This example differs from Example 30 in that 3 / 4 of A copper tungsten feed and 1 / 2 of B copper tungsten feed are mixed and injected into the mold at 80 MPa, and the pressure is maintained for 3 seconds.

[0093] Example 33: The difference between this example and Example 30 is that the center of the spider-web-shaped groove coincides with the center of the bottom layer, and the minimum radius of the spider-web-shaped groove is 1 / 10 of the length of the bottom layer, and the radius of each circle of the spider-web-shaped groove from the inside to the outside is 1.2 times the radius of the previous circle, and the skeleton line of the spider-web-shaped groove is radial along the minimum radius, and there are 10 skeleton lines at equal angles, and the depth of the spider-web-shaped groove is 1 / 2 of the thickness of the bottom layer.

[0094] Example 34: The difference between this example and Example 30 is that the center of the spider-web-shaped groove coincides with the center of the bottom layer, and the minimum radius of the spider-web-shaped groove is 1 / 8 of the length of the bottom layer, the radius of each circle of the spider-web-shaped groove from the inside to the outside is 1.3 times the radius of the previous circle, the skeleton line of the spider-web-shaped groove is radial along the minimum radius, and there are 15 skeleton lines at equal angles, and the depth of the spider-web-shaped groove is 3 / 5 of the thickness of the bottom layer.

[0095] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.

[0096] The density test and thermal conductivity test were performed three times on each embodiment, and the average results were used as the density and thermal conductivity of the copper-tungsten heat sink material of each embodiment.

[0097] 1. Investigate the influence of W content and the proportion of plastic-based binder components on the performance of copper-tungsten heat sink materials.

[0098] Table 1 Performance of copper-tungsten heat sink materials in Examples 1 to 6

[0099]

[0100]

[0101] It can be seen from the results in Table 1 that the various relevant properties of the copper-tungsten heat sink material prepared by the W content range and plastic-based binder selected in this application can meet the use requirements, and by comparison, it can be seen that the density and thermal conductivity of Example 1 / 2 are obviously greater than those of Examples 3 to 6, so the heat sink effect of Example 1 / 2 is better.

[0102] Figure 1 and Figure 2 They are the morphology of the fracture of the CuW80 injection molded product obtained in Example 1 observed under a 500x and 1000x electron microscope after destruction and fracture, wherein the tungsten particles show transgranular cleavage fracture, which means that the mechanical properties of CuW80 are high, and the high mechanical properties such as high hardness of the injection molded product prepared by the present invention are confirmed from the microstructure; the copper phase fracture shows dimples, which means that the material has good plasticity and toughness, and the high bending strength characteristics of the injection molded product are confirmed from the microstructure;

[0103] Figure 3 and Figure 4 These are the metallographic images of CuW80 injection molding at 100 times and 200 times respectively. In the image, blue is tungsten and yellow is copper. The addition of organic binder and surfactant in the injection molding process makes the tungsten powder more dispersed. The absence of defects such as pores in the image proves that the product has a good effect after injection molding.

[0104] Figure 5 and Figure 6 They are the metallographic images of CuW80 prepared by conventional process (high temperature sintering of molded skeleton + infiltration) at 100 times and 200 times respectively. It can be seen that compared with the metallographic image of the injection molded product obtained in this application, the tungsten particles are interconnected to form a sintering neck with high connection strength and difficult machining.

[0105] 2. Investigate the influence of various preparation parameters on the density and thermal conductivity of copper tungsten heat sink materials.

[0106] Table 2 Density and thermal conductivity of copper tungsten heat sink materials in Examples 7 to 22

[0107]

[0108] From the above results, it can be seen that the preparation parameters of the gel are too small or too large, the redox parameters are too small or too large, the particle size difference between the precursor powder and the copper-tungsten composite powder is too small or too large, the copper-tungsten feeding softening parameters are too small or too large, the pressing parameters are too small or too large, the oxalic acid degreasing parameters are too small or too large, the thermal degreasing parameters are too small or too large, and the sintering parameters are too small will all reduce the density and thermal conductivity of the copper-tungsten heat sink material. The larger sintering parameters in Example 22 result in greater density and thermal conductivity than in Example 1, but the performance improvement is smaller than the improvement in the sintering parameters. Therefore, from a cost perspective, the parameter effect of Example 1 is better.

[0109] 3. Investigate the effect of core-shell gel on the thermal conductivity of copper-tungsten heat sink materials.

[0110] Table 3 Thermal conductivity of copper-tungsten heat sink materials in Examples 23-29 and Comparative Examples 1-2

[0111]

[0112] The difference between Control Example 1 and Example 23 is that the second gel is not subjected to directional freezing;

[0113] The difference between Control Example 2 and Example 23 is that the stretched first gel serves as the core-shell, and the frozen stretched second gel serves as the core;

[0114] From the above results, it can be seen that compared with Example 1, Example 23 to Control Example 2 all improve the thermal conductivity. Since the influence of density is small, the density is not displayed in the table data, but the thermal conductivity can still prove that the core-shell gel further enhances the performance of the copper-tungsten heat sink material compared with the method of obtaining the gel by overall mixing;

[0115] Control Example 1 lacks directional freezing, and Control Example 2 swaps the core and the core-shell, both of which reduce the improvement in thermal conductivity compared to Examples 23 to 29. Therefore, the gel design of Examples 23 to 29 is more reasonable. By comparing Examples 23 to 29, it can be seen that too small or too large a mass of the second gel, too small or too large a stretching multiple of the first gel, and too small or too large parameters of the second gel freezing and stretching will all reduce the improvement in thermal conductivity. Therefore, relatively speaking, the parameter effect of Example 22 is better.

[0116] 4. Investigate the effect of spider-web grooves on the density and thermal conductivity of copper-tungsten heat sink materials.

[0117] Table 4 Density and thermal conductivity of copper tungsten heat sink materials in Examples 30 to 34

[0118]

[0119] From the above results, it can be seen that, compared with Example 23, Examples 30 to 34 design the structure of the injection molded semi-finished product as a spider web-shaped groove combination, which can significantly improve the density and thermal conductivity of the copper-tungsten heat sink material, and the change of parameters has a small impact on the performance, so the performance is relatively stable;

[0120] By comparing Examples 30 to 34, it can be seen that if the mixing ratio of copper tungsten feed A and copper tungsten feed B is too small or too large, and the skeleton line and depth of the spider-web-shaped groove are too small or too large, the density and thermal conductivity of the copper tungsten heat sink material will be slightly reduced. In comparison, the parameter effect of Example 30 is relatively better.

[0121] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present application. It should be understood that the above description is only a specific embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder, characterized in that: The following steps are involved: S1. Mixing and granulation: Add a plastic-based binder to a copper-tungsten composite powder in which W accounts for 60-95wt% in a nitrogen atmosphere with an oxygen content of less than 0.01%, stir and knead for 1.5-3h at 170-180°C and 30-50r / min to obtain a mixture, extrude and chop it, and obtain a copper-tungsten feed with a particle size of 1-3μm; The amount of the plastic-based binder added is 10-15wt% of the mixture, and the plastic-based binder, by mass percentage, includes: 3-5% high-density polyethylene, 3-6% ethylene bisstearamide, 0.5-2% phosphotungstic heteropoly acid, 0.5-2% salicylic acid, and the balance polyformaldehyde, wherein the polyformaldehyde is any one or more of polyformaldehyde 5520 and polyformaldehyde 4520; S2. Injection molding: The mold is preheated to 75-95° C., the copper-tungsten feed obtained in step S1 is softened at a temperature of 145-170° C. for 2-3.5 hours, and then the softened copper-tungsten feed is injected into the mold at a pressure of 80-120 MPa, and the pressure is maintained for 1-3 seconds, and then demolded to obtain an injection molded semi-finished product; S3, degreasing and sintering: After degreasing the injection molded semi-finished product obtained in step S2, the temperature is continuously raised to 1080-1200° C. at a rate of 1-3° C. / min and kept at this temperature for 4-6 hours to obtain a tungsten-copper heat sink material.

2. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 1, characterized in that: The preparation method of the copper-tungsten composite powder comprises the following steps: ammonium paratungstate, soluble copper salt and organic acid solution are mixed in a mass ratio of 12:25-300:60-756 to obtain a gel, and the gel is dried at 250-400° C. to obtain a precursor powder; The precursor powder is calcined at 500-700° C. for 3-6 hours to obtain a copper-tungsten composite oxide, and then the copper-tungsten composite oxide is reduced at 750-880° C. for 3-5 hours in a hydrogen-containing atmosphere to obtain a copper-tungsten composite powder.

3. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 2, characterized in that: The soluble copper salt is selected from any one of copper nitrate and copper sulfate, and the organic acid solution is a citric acid solution with a mass concentration of 50-60%.

4. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 2, characterized in that: The hydrogen-containing atmosphere is any one of hydrogen, hydrogen-argon mixed gas or hydrogen-carbon monoxide mixed gas, wherein the hydrogen content is 95-100%.

5. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 2, characterized in that: The method for obtaining the gel by mixing is: stirring at 70 to 95° C. at a frequency of 30 to 60 Hz for 1 to 2 hours to obtain the gel.

6. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 1, characterized in that: The particle size of the precursor powder is 0.2-1.5 μm, and the particle size of the copper-tungsten composite powder is 200-700 nm.

7. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 1, characterized in that: In step S2, the method of injecting the softened copper-tungsten feed into the mold is: The copper tungsten feed is divided into A copper tungsten feed of 1-2 μm and B copper tungsten feed of 2-3 μm according to the particle size; 1 / 2 to 3 / 4 of A copper-tungsten feed and 1 / 2 to 3 / 4 of B copper-tungsten feed are mixed and injected into the mold at 50 to 80 MPa, and the pressure is maintained for 1 to 3 seconds to serve as the bottom layer, and then a spider-web-shaped groove is etched on the surface of the bottom layer, and the depth of the spider-web-shaped groove is 1 / 2 to 3 / 5 of the thickness of the bottom layer; wherein the center of the spider-web-shaped groove coincides with the center of the bottom layer, and the minimum radius of the spider-web-shaped groove is 1 / 8 to 1 / 10 of the length of the bottom layer, and the radius of each circle of the spider-web-shaped groove is 1.2 to 1.3 times the radius of the previous circle from the inside to the outside, and the skeleton line of the spider-web-shaped groove is radially arranged along the minimum radius, and 10 to 15 skeleton lines are arranged at equal angles; Finally, the remaining A copper tungsten feed and B copper tungsten feed are injected into the groove with the same injection parameters as the bottom layer, and the injection is completed.

8. The method for preparing a tungsten-copper heat sink material from a tungsten-copper composite powder according to claim 1, characterized in that: In step S3, the degreasing method is: under a nitrogen atmosphere, oxalic acid with a mass concentration of 10-20% is added to the injection molded semi-finished product obtained in step S2 at a rate of 2-5 g / min, degreasing at 110-130° C. for 2-4 hours, and then continuously heating to 580-620° C. at 1-3° C. / min in a hydrogen atmosphere and keeping the temperature for degreasing for 2-3 hours.

9. A tungsten copper heat sink material, characterized in that: The tungsten-copper heat sink material is prepared by the method for preparing tungsten-copper composite powder according to any one of claims 1 to 8.